Niobium oxide (Nb2O5) as support for CoMo and NiW catalysts in the hydrodesulfurization reaction of 3-methylthiophene (Research, Society and Development, 2020)
The efficiency of niobium oxide as catalytic support of hydrodesulfurization (HDS) catalysts (CoMo and NiW) has been investigated in the HDS of a model molecule representative of sulfur compounds present in FCC gasoline (3-methylthiophene: 3MT). The NiW catalyst presented higher catalytic activity than CoMo calcined and non-calcined catalyst, however a better ratio pentane/pentene has been achieved by CoMo catalysts, which implies a lower formation of hydrogenated products. Indeed, the activity order for the catalysts evaluated is: NiW/Nb2O5 > CoMo/Nb2O5 calcined support > CoMo/Nb2O5 non-calcined support, despite the ratio pentane/pentene which has the inverse order. Furthermore, textural and chemical characterization techniques have been performed. From NH3-TPD analysis it was observed an acidity profile with a predominance of weak/strong and weak/moderate acid for CoMo and NiW catalysts, respectively. Meanwhile, the BET analysis has shown a low specific surface area for the catalysts supported by niobium oxide. Concerning the structure characteristic, the XRD analysis has suggested an amorphous phase in all catalysts analyzed.